Israeli FDI in the Dubai Real Estate Market: Motives and Barriers - Sharon, Roi (Digital Repository of Theses, 2024)
This research examines the attractiveness of the Dubai real estate market among Israeli physical persons, following the authorization of the Israel–UAE peace agreement in [2020], and maps the motives and barriers that might promote or restrain their integration into the Dubai immovables market in the subsequent years, 2021–2025. Eight months after the signing of the ‘Abraham Accords’, an anonymous internet-mediated questionnaire was administered to gather primary standardized data from a sample consisting of 201 adult Israeli nationals (N = 201). The empirical results show that prospective Israeli FDI in the Dubai real estate market between 2021 and 2025 is influenced by seven motives (the Israel–UAE tax treaty preventing double taxation, the absence of personal income tax in the UAE, the UAE non-imposition of corporate tax, the high number of tourists visiting this particular region of the UAE, the expected expansion of Dubai’s economy, the anticipated increase in real estate values in the Emirate of Dubai, and the diversification of investments) and 11 barriers (potential political instability between Israel and the UAE, government restrictions on foreign ownership of property and land, discriminatory treatment at the governmental or civil levels, travel restrictions, potential low returns on real estate investments, unfavourable regulatory and legal frameworks, macroeconomic instability, designated free trade zones, bureaucracy, exchange rate volatility, and differences in business mentality). Overall, the sample was dominated by subjects who were extremely unlikely to invest in plots or any properties designated for industrial, commercial, or residential purposes in the Emirate of Dubai over the years 2021 to 2025. Due to time and resource constraints, the research exclusively investigated the Dubai real estate market, and thus its conclusions may not be suitable for other emirates or for the entire UAE.